2020
DOI: 10.1155/2020/4178674
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Taste Threshold Sensitivity and MMP-9, Salivary Secretion, Blood Pressure, and Blood Glucose Levels in Smoking and Nonsmoking Women

Abstract: Cigarette smoking can cause taste receptors to increase the taste threshold value. Consequently, the consumption of sugar and salt will not be controlled, therefore causing systemic diseases such as hypertension and diabetes. Nicotine and tobacco in cigarettes can stimulate MMP-9 which plays vital physiological roles in normal tissue growth and repair processes. This study aimed to find the correlation between taste threshold sensitivity and MMP-9, salivary secretion, blood pressure, and blood glucose levels i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Decreased taste sensitivity leads to higher calorie, salt, and fat intake, causing an increase in BMI [ 28 ]. Lower taste sensitivity is also associated with higher blood pressure in female smokers [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Decreased taste sensitivity leads to higher calorie, salt, and fat intake, causing an increase in BMI [ 28 ]. Lower taste sensitivity is also associated with higher blood pressure in female smokers [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that for DM patients, the salivary glucose level is positively correlated with the blood glucose level, so salivary glucose can be used as a marker for DM detection [ 23 , 24 ]. However, in different studies, the relationship between salivary glucose and blood glucose is quite different with completely opposite conclusions, pointing out that salivary glucose and blood glucose have no significant correlation [ 25 , 26 ]. The key factor contributing to this phenomenon is that saliva is collected differently, and most studies view saliva wrongly as a homogeneous body fluid.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that there were two types of STT measurements, namely whole-mouth (Adolf et al, 2021;Amen, 2015;Fayasari & Cahyani, 2022;Cho et al, 2016;Kim et al, 2017;Kubota et al, 2018Martinelli et al, 2020Piovesana et al, 2013;Son et al, 2015;Tjahajawati et al, 2020;Veček et al, 2020) and salt-impregnated taste strips (Kubota et al, 2018;Torigoe et al, 2019). Salt-impregnated taste strips eliminated the drawbacks of the wholemouth approach.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen studies that examined STT and hypertension had an age between 18 -78 years. The most age categories are old adults with an average age of more than 45 years (Amen, 2015;Azotea, Cruz, & Barcelon, 2013;Cho, Kim, Jeong, & Kim, 2016;Kim, Ye, & Lee, 2017;Piovesana et al, 2013;Son et al, 2015;Veček et al, 2020), followed by young adults or 17-30 years old (Martinelli, Conde, de Araújo, & Marcadenti, 2020;Tjahajawati, Rafisa, Murniati, & Zubaedah, 2020), middle-age adults or 31-45 years old (Adolf et al, 2021;Fayasari & Cahyani, 2022, and elderly or up to 60 years old (Kubota et al, 2018;Torigoe et al, 2019;Xue et al, 2020).…”
Section: Subject Characteristicmentioning
confidence: 99%
See 1 more Smart Citation